(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study examines the implementation of the Special Sports Class (KKO) Program at SMP Negeri 1 Kendal, which aims to develop students’ potential in sports. This program is supported by policies from the Kendal Regency Education Office and involves collaboration between various parties, including teachers, coaches, and parents. The research method used is qualitative analysis to identify supporting and inhibiting factors in program implementation. The results show that despite strong support from various parties, challenges remain, such as student fatigue and a lack of infrastructure. This research is expected to provide insights for the development of sports programs in other schools.